Pengembangan Metode Prakonsentrasi dengan Teknik Injeksi Alir untuk Analisis Cu2+ dan Pb2+ dalam Air Aliran Sungai Citarum dan Waduk Saguling - Saepudin Suwarsa; Buchari Buchari; Aman Sentosa Panggabean (Jurnal Matematika & Sains, 2008)
A research aiming at developing preconcentration method using ion exchange resin column for Cu2+ and Pb2+ ionsanalysis in the stream of Citarum river and the Saguling lake has been carried out. The preconcentration method wasperformed using a mini column filled with Dowex 50W-X8. The preconcentration method was developed to beincorporated with the flow injection analysis (FIA), for which water samples were passed through the mini column andby eluting with 3 M HCl, and the eluate was detected by an atomic absorption spectrophotometer detector. The optimalconditions for the best analytical performance with FIA-AAS method were 5 mL injection volume of waters samples, theeluent HCl concentration was 3 M and the volume was 1 mL. The limit of detection achieved by this method for Cu andPb ions were 5.26 dan 24.57 ppb, respectively. The reproducibility level shown by the coefficient of variance for thismethod was 2.11%. The method was applied to natural water samples with a recovery percentage of > 95%. The spikemethod develoved in this research, for matrices of water sample from Citarum river and the Saguling lake, has itsadvantage that the matrices did not affect the results of measurements.